1974
DOI: 10.1073/pnas.71.4.1065
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Spectra of Cobalt-Substituted Hemoglobin: Cooperativity and Displacement of the Cobalt Atom upon Oxygenation

Abstract: The resonance Raman spectra of oxy and deoxy cobalt-substituted hemoglobin (CoHb) are reported. Comparison of these spectra to those of hemoglobin, methemoglobin, cytochrome c, and model cobalt porphyrin complexes suggests that the displacement of the cobalt atom upon oxygenation of CoHb is no greater than the out-of-plane distance in five-coordinate Co(II) porphyrins, 0.15 A. Combining this distance with the expected contraction of the cobalt-histidine bond, Ibers has estimated a maximum displacement of 0.37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…The orientation and the source of rotational barriers in the Zeise's salt complexes, 3, are actually set by steric factors.27®-32 It takes something as large as a feri-butyl group on, for example, a benzene ring to cause an appreciable effect on the rotational potential for a compound where there is normally a small barrier. [23][24][25][26][27][28][29][30][31][32][33] In systems possessing a much larger barrier such as the acyclic polyene-ML3 class there are a number of examples34 where extremely close contacts exist between substituents on the polyene ring and the (31) Albright, T. A. J. Organomet. Chem.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…The orientation and the source of rotational barriers in the Zeise's salt complexes, 3, are actually set by steric factors.27®-32 It takes something as large as a feri-butyl group on, for example, a benzene ring to cause an appreciable effect on the rotational potential for a compound where there is normally a small barrier. [23][24][25][26][27][28][29][30][31][32][33] In systems possessing a much larger barrier such as the acyclic polyene-ML3 class there are a number of examples34 where extremely close contacts exist between substituents on the polyene ring and the (31) Albright, T. A. J. Organomet. Chem.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…These wavenumbers are similar to those reported for 6-coordinated low spin bis-pyridine Co IIIporphyrins and for oxy-cobaltous-globins (Table S4, ESI †). 20,21 Accordingly, they may be indicative of a 6-coordinated low spin complex. However, it is difficult to definitely assign spin and coordination states to Co III -MC-6, due to the lack of reference rR data on 5-coordinated cobaltic porphyrin complexes.…”
mentioning
confidence: 99%
“…Chien and Dickinson, 1972;Dickinson and Chien, 1973a,b;Woodruff et al, 1974;Yonetani et al, 1974) showed that it is the motion of the proximal histidine, but not that of the metal ion, with respect to the heme plane which constitutes the necessary and sufficient condition for the triggering of the allosteric transition.…”
mentioning
confidence: 99%